(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, we will focus mainly on the productivity of the educational process within the framework of ergonomic requirements, the improvement of the educational process has not yet been studied. In the context of increasing automation, technization and informatization of education, there is a need for ergonomic research within the framework of requirements. Improving the educational process initially, ergonomics is understood as a science that studies systems, laws.